Предмет:
Другие предметыАвтор:
анонимИспользуем следующие формулы:
(ctg (x) )\' = - 1 / sin2 (x);
(f (g (x) ) )\' = (f (g) )\' * (g (x) )\';
(x)\' = 1;
(C)\' = 0, где C - константа;
(u + v)\' = (u)\' + (v)\'.
(y)\' = (ctg (10 * x + 14) )\' = (- 1 / sin2 (10 * x + 14) ) * (10 * x + 14)\' =
= (- 1 / sin2 (10 * x + 14) ) * ( (10 * x)\' + (14)\' ) =
= (- 1 / sin2 (10 * x + 14) ) * (10 * (x)\' + 0) = (- 1 / sin2 (10 * x + 14) ) * (10 * 1) =
= - 10 / sin2 (10 * x + 14).
Ответ: (- 10 / sin2 (10 * x + 14) ).
Автор:
snoopyo3rtДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть